The effectiveness of a participatory program on fall prevention in oncology patients. Issue 2 (8th December 2014) - Huang, Li-Chi; Ma, Wei-Fen; Li, Tsai-Chung; Liang, Yia-Wun; Tsai, Li-Yun; Chang, Fy-Uan
Abstract : Falls are known to be one of the most common in patient adverse events. A high incidence of falls was reported on patients with cancer. The purpose of this study was to explore the effect of a participatory program on patient's knowledge and self-efficacy of fall prevention and fall incidence in an oncology ward. In this quasi-experimental study, 68 participants were recruited at a medical centre in Taiwan. A 20-min fall prevention program was given to patients. A questionnaire was used to evaluate the effectiveness of program after on day 3 of intervention. The data of fall incidence rates were collected from hospital record. Fall incidences with and without the program were used to compare the effectiveness of intervention. The patients' knowledge and self-efficacy of fall prevention are better than after intervention. A statistically significant difference in fall incidence rate was observed with (0.0%) and without (19.3%) the program. Our findings suggest that the fact of the bedside is that the most risk for falling in hospital must be communicated to the hospitalized patients. Educating patients about fall prevention and activities associated with falling increases their awareness of the potential of falling and promoting patient safety.